High performance nanoscale imaging with table-top high harmonic sources - Tadesse, G. K.; Klas, R.; Eschen, W.; Tuitje, F.; Steinert, M.; Spielmann, C.; Pertsch, Thomas; Tünnermann, A.; Limpert, Jens; Rothhardt, J. (Proceedings of SPIE - The International Society for Optical Engineering, 2018)
Todays high harmonic sources provide high photon flux, short wavelengths and excellent coherence. We will present a number of experiments, including record-13 nm resolution imaging, which have been performed with fiber laser driven XUV sources.
CRIS-Team Scopus Importer:2023-04-20